FORMULATION AND ANTIOXIDANT ACTIVITY TEST OF PEEL OFF GEL MASK KOMBUCHA BUNGA TELANG USING THE DPPH METHOD - Yayan, Rizikiyan; Fasiha Nur, Fadila; Ine, Suharyani; Renny, Amelia (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2025)
Free radicals are unpaired molecules that can cause damage to body cells. This cellular damage can be countered with natural antioxidants derived from plants, one of which is butterfly pea flower, when combined with kombucha, resulting in butterfly pea kombucha that has better antioxidant activity for the body. Peel-off gel masks are facial cosmetic preparations that have a gel-like consistency when applied to the face. After a certain period, they dry and form a film layer that can be peeled off. The concentrations of butterfly pea flower kombucha used were 5%, 7.5%, and 10%. The purpose of the study was to determine the antioxidant activity of the butterfly pea flower kombucha peel-off gel mask using the DPPH method and to obtain the optimum formula. The DPPH method was used to assess the ability of the antioxidant activity to inhibit DPPH. The evaluation of the peel-off gel mask formulation was conducted through organoleptic testing, homogeneity, pH, spreadability, adhesion, drying time, viscosity, and flow properties. To determine antioxidant activity, antioxidant activity testing was performed using a UV-Vis spectrophotometer. The results of the evaluation of the peel-off gel mask formulations 1, 2, and 3 fulfill all testing requirements, with antioxidant activity showing IC50 values of 56.03 ppm ± 0,02 for Formula 1, 52.50 ppm ± 0,02 for Formula 2, and 49.32 ppm ± 0,04 for Formula 3